Rhinosporidiosis of the lacrimal sac masquerading as chronic dacryocystitis: a rare presentation - Pradhan, Pradeep; Samal, Swagatika (Autopsy and Case Reports, 2021)
Rhinosporidiosis is a chronic infection of the mucous membrane caused by the Rhinosporiduim seeberi, which infects through transepithelial penetration. Although described worldwide, this entity is mostly found in the western hemisphere, afflicting young people, predominantly males, associated in many cases with recreational or professional contact with bath in ponds, rivers, or stagnant waters. The clinical features are varied depending on the affected membrane, in some cases mimicking other diseases postponing the correct diagnosis. Although nasal obstruction and epistaxis are the common clinical presentations in sinonasal rhinosporidiosis, patients with epiphora without a nasal mass often challenge the diagnosis. In the present case, we have documented a case of isolated lacrimal sac rhinosporidiosis masquerading as chronic dacryocystitis, which was successfully managed by endoscopic excision, accompanied by a literature review.